The phenomenology of spirit - Hegel, Georg Wilhelm Friedrich, 1770-1831; Fuss, Peter; Dobbins, John (Notre Dame : University of Notre Dame Press, 2019)
"The Phenomenology of Spirit, first published in 1807, is G.W.F. Hegel's remarkable philosophical text that examines the dynamics of human experience from its simplest beginnings in consciousness through its development into ever more complex and self-conscious forms. The work explores the inner discovery of reason and its progressive expansion into spirit, a world of intercommunicating and interacting minds reconceiving and re-creating themselves and their reality. The Phenomenology of Spirit is a notoriously challenging and arduous text that students and scholars have been studying ever since its publication. In this long-awaited translation, Peter Fuss and John Dobbins provide a succinct, highly informative, and readily comprehensible introduction to several key concepts in Hegel's thinking. This edition includes an extensive conceptual index, which offers easy reference to specific discussions in the text and elucidates the more subtle nuances of Hegel's concepts and word usage. This modern American English translation employs natural idioms that accurately convey what Hegel means. Throughout the book, the translators adhered to the maxim: if you want to understand Hegel, read him in the English. This book is intended for intellectuals with a vested interest in modern philosophy and history, as well as students of all levels, seeking to access or further engage with this seminal text"--
3. Total Freedom and TerrorVI. C. Spirit Certain of Itself: Morality; a. The Moral World-View; b. Misrepresentation; c. Conscience; the Beautiful Soul: Evil and Its Forgiveness; CHAPTER VII. Religion; VII. A. Natural Religion; a. The Divine Light; b. Plant and Animal; c. The Artificer; VII. B. Art-Religion; a. Abstract Artwork; b. Living Artwork; c. Spiritual Artwork; VII. C. Manifest Religion; CHAPTER VIII. Absolute Knowing; Conceptual and Topical Index
Online resource; title from digital title page (viewed on September 17, 2019).
Includes bibliographical references and index.
Translated from German.
eBooks on EBSCOhost
Keywords: Spirit; Consciousness; Truth; Esprit; Conscience; Vérité.; truth; Consciousness; Spirit; Truth; Electronic books